Diversity and Agronomic Performance of 20 Local Cowpea Cultivars (Vigna unguiculata (L.) Walp.) in Burkina Faso - Pingawindé Sawadogo; Karidiatou Gnankambary; Benoit Teyioué Joseph Batieno; Minata Ilboudo; Astrid Ella Kabore; Soungalo Soulama (HAYATI Journal of Biosciences, 2026)
Vigna unguiculata is one of the main legumes consumed in Burkina Faso. Its genetic improvement requires a good understanding of the diversity of local cultivars. However, very little information exists on these local cultivars. This study aims to contribute to a better understanding of the diversity and agronomic performance of cowpea cultivars in Burkina Faso. The plant material studied consists of 20 cowpea cultivars, 17 of which are from the National Commission for Plant Genetic Resources Management (SP-CONAGREP) and three from the Institute of Environment and Agricultural Research (INERA). The experimental design was a randomized block with three replications. The experiment was conducted over two farming seasons in 2022 and 2023. The quantitative variables measured are related to phenology and yield. The results revealed cultivars with white flowers and violet flowers. For yield-related performance, the results showed that the Sanga and CSI01 cultivars were the most productive in terms of number of seeds per pod in 2022. Performance varies by cultivar and year and is influenced by climatic and environmental conditions. The DANPLA cultivar achieved the highest 100-seed weight in 2022 and 2023, at 17.03 g and 19.43 g, respectively. The structuring of the 20 cultivars in the collection resulted in four groups based on agronomic performance. Group I consists of early-cycle cultivars and is characterized by large seeds. These important traits can be exploited in breeding programs.